PERAN E-COMMERCE DALAM MENINGKATKAN PEREKONOMIAN LOKAL DI ERA DIGITAL - Gunawan Widjaja (Prosiding Seminar Nasional Indonesia, 2025)
The important role of e-commerce in improving the local economy in the digital era by focusing on the empowerment of Micro, Small and Medium Enterprises (MSMEs). E- commerce provides wider market access for MSMEs, opening up sales opportunities to the global level without geographical restrictions. Digital literacy and adequate internet infrastructure are key elements that enable local businesses to run online businesses eflectively, thereby improving their operational efficiency and competitive ability. In addition, the optimisation of logistics and the implementation of appropriate digital marketing strategies contribute to the success of e-commerce in supporting the local economy. With efficient logistics infrastructure and modern technology, MSMEs can fulfil consumer expectations for fast and safe delivery. Data-driven digital marketing strategies help MSMEs attract and retain customers. Overall, e-commerce is creating new opportunities for local businesses and driving inclusive and sustainable economic growth.